Negotiating Trans Affect in Luka Holmegaard’s Havet i munden - Tais Terletskaja (Kvinder, Køn & Forskning)
Identifying a dominant affective polarization pertaining to contemporary trans discourse and the constraints this poses in accounting for trans experience, the article turns to the sphere of trans poetics. Through a reading of Havet i munden (2023) [The Ocean in Your Mouth] by Danish author Luka Holmegaard, the article discerns poetic strategies for navigating the politically pressurized present. The article argues that in troubling the relation between pleasure and pain, exhibiting representational restraint, and attuning to bodily sensations, Havet i munden offers a renegotiation of trans affect, exhibiting the desire to move beyond the constraints of marked identity entirely.